Characterizing the 3-Dimensional Printability of Alginate–Gelatin and Nanocellulose Gels via Fringe Projection - Anush Lakshman; Yanhua Huang; William Bussey; Lingling Liu; Beiwen Li (Advanced Devices & Instrumentation)
Gelatin-based hydrogels have been preferred in biomedical applications such as tissue engineering, drug delivery, and lens fabrication due to their biocompatibility, biodegradability, and mechanical stability. Three-dimensional (3D) printing enables the fabrication of complex structures demanded by these applications. While material selection and parameter optimization are crucial preparatory steps for 3D printing, current methods rely on 2D imaging techniques for quality assessment and feedback control. These methods have limited resolution and are sensitive to ambient lighting and substrate color, leading to characterization errors. This paper presents a 3D evaluation method based on fringe projection profilometry (FPP) to overcome the limitations of existing techniques. The proposed approach enables material and extrusion rate selection by quantifying lateral and z-axis deviations in strand prints caused by improper extrusion, using a telecentric fringe projection system. We validate this method by evaluating 7 sodium alginate–gelatin hydrogel combinations with varying component concentrations. Final validation is conducted by printing a test capsule, imaging the freeze-dried print using a conventional FPP system, and analyzing its structural conformance.